Pengaruh Motivasi Berprestasi dan Minat Belajar Terhadap Hasil Belajar Bahasa Inggris Siswa Kelas XI IPS SMA Dian Andalas Padang - Nur Syahadani Putri; Fitria Ariani (Universitas Muria Kudus, 2023)
This research aims to determine the influence of achievement motivation and interest in learning on the English learning outcomes of class XI IPS students at Dian Andalas High School, Padang. This type of research is descriptive and associative. The population in this study were all students in class XI IPS at SMA Dian Andalas Padang, totaling 130 students. The sampling technique used was proportional random sampling. The number of samples in this research was 98 students. The data analysis techniques used are descriptive analysis and inferential analysis.The results of multiple regression show that (1) Achievement motivation has a significant positive effect on students' English learning outcomes. (2) Interest in learning has a significant negative effect on students' English learning outcomes. (3) Achievement motivation and interest in learning have a significant effect on students' English learning outcomes together.Based on the research results, it is recommended that schools, subject teachers and guidance and counseling teachers provide equal opportunities for all students to take part in various academic competitions that suit the students' potential. This will help grow students' motivation to excel and help increase students' interest in learning to be even better.Keywords: Achievement Motivation, Interest in Learning and English Learning Results.